Numerical Study on the Massive Outbreak of the Ulva prolifera Green Tides in the Southwestern Yellow Sea in 2021 - Bin Wang (MDPI AG, 2021)
The most massive outbreak on record of the Ulva prolifera green tides in the southwestern Yellow Sea occurred in summer of 2021. The environmental factors were investigated based on observations and simulations. The results suggested that the significantly enhanced discharge of the Changjiang River since winter 2020–2021 was crucial for the outbreak of the Ulva prolifera green tides in the southwestern Yellow Sea, which could significantly have contributed to the nutrient enrichment off the Subei coast. Additionally, the southerly wind stress anomaly during winter 2020–2021 favored the upwind transport of Changjiang water. Numerical experiments showed that the remaining winter freshwater coming from the Changjiang River, which persisted in the Subei coast’s upper layer until spring 2021, exceeded the long-term average value by 20%. We demonstrated that these large amount of nutrient inputs, as an effective supplement, were the reason the green tides sharply emerged as an extensive outbreak in 2021. The easterly wind anomaly during spring 2021 contributed to the landing of Ulva prolifera off the Lunan coast.